Impact of Commonly Used Epibiotics on the Water Quality in Shrimp Grow out Ponds Bordeing the Dutch Canal-Mundel Lagoon - Corea, A.S.L.E.; Jayasinghe, J.M.P.K. (NARA, Sri Lanka, 2002)
Use of epibiotics in shrimp culture, to control water quality, became popular with the necessity to reduce water exchange, as a precaution against disease out-breaks. Several different brands of epibiotics (bacterial cultures) have been introduced to Sri Lanka. However the effectiveness of these bacterial cultures have not been assesed and many farmers felt that these bacterial cultures were not effective. This study was conducted to investigate the effects of two commonly used probiotics on the water quality of shrimp growth ponds. The study was carried out in 10 different sites in the Mundel - Dutch Canal area and the selected ponds were treated with two common bacterial cultures (BC1 and BC2) with a control provided with the same conditions. Water quality was monitored weekly and the results were analysed statistically to find any significant difference in the water quality. Bacterial cultures were applied weekly as instructed. The results revealed a significant difference (p>0.05)between Bc2 and other 2 treatments with respect to Nitrite, Sulphide and ammonia. However, BC1 showed no significant water quality changes (p<0.05)with respect to Nitrite, and Ammonia levels between the treatment and control ponds. BC2 showed significant difference (p>0.05) in the Nitrite levels from the 1st week after treatment while BC2 also showed a significant difference in the sulphide levels after the 2nd week.